Target-Controlled Infusion - V. Holly; M Ondercianin; P. Mendel; M. Liska; M. Jaroslava (Общая реаниматология, 2009)
In this article the authors present a brief review of the development of intravenous anesthesia, from its beginnings to today’s widely accepted use of the TCI technique. They explain the theory of TCI based on the pharmacokinetic properties of drugs. They point out undeniable advantages that this technique offers, compared to classical intravenous anesthesia and even inhalational anesthesia. They offer a short description of basic technological characteristics of a TCI pump. At the end of the article they present their own experiences with this technique, with the aim to bring it closer to a wider qualified public. Key words: intravenous anesthesia, total intravenous anesthesia, TCI.